Does carbon-conscious behavior drive firm performance? an event study on the Global 500 companies - Renner, Adrian (Springer eBooks., 2011)
Climate change and its implications for consumers and policymakers, have been discussed extensively. Adrian Renner provides a unique perspective on how stockholders react if companies move towards a carbon-conscious future. A multi-country event study approach was used to analyze stock market reactions of the largest 500 companies globally. The analysis shows that depending on the situation of the company outcomes vary substantially. For example, Asian companies were gratified by investors for their carbon-conscious behavior while European and North American companies got punished for this.